Aggregated calculation of the weighted average cost of capital of companies - A. J. Kukharenko; A. A. Stern; M. A. Gorsky (Путеводитель предпринимателя)
A key indicator of the efficiency of the production sector of the enterprise in competitive commodity and financial markets is the weighted average cost of capital involved in the financing of production and non-production costs. The Corporation is equally interested in its high market capitalization and in reduction of the cost of attracted capital. Therefore, the correct assessment of the cost of equity and debt financing, as well as the weighted average cost of capital is the important part of financial management. These assessments currently use the model of the cost of capital assets (CAMP), models, portfolio theory (Markowitz - Torbin - sharp) and also various versions of the model weighted average cost of capital (WACC), for example, R. Hamada. In this article, the authors on the basis of comparison of known approaches particularly highlight the method of estimating the weighted average cost of capital proposed by D. Bezukhov and M. Khalikov. It is adapted to Russian conditions and shows adequate estimates of the cost of capital. However, this method and some other options proposed by the same authors are multi-step and difficult to implement. In order to increase the practical significance of this algorithm, we propose a «one-step» formula that provides for a uniform procedure for calculating the weighted average cost of capital of Russian companies based on a universal formula. On the basis of the proposed formula, the calculation of the weighted average cost of capital of PLC MMC Norilsk Nickel, ALROSA, PLC Severstal, Anglo American PLC, China Shenhua Energy Company, Vale S. A., Rio Tinto Group, Teck Resources Limited, BHP Billiton are given, which convincingly testify to its practical value.